Cooking Palm Oil Price Control Policies in Indonesia: Abu Yusuf's Islamic Economic View - Fitra Rizal (Journal of Islamic Economics (JoIE), 2022)
This study aims to determine the views of Abu Yusuf's Islamic economy on the policy of controlling cooking oil prices in Indonesia. The research method used is a qualitative research methodology with a library research approach. The results show that the market mechanism in Islam is free without any intervention. This means that the price in the market is determined by the level of demand and supply that is fair (fair price). However, the Government can intervene in the market price when there is market distortion. So that when cooking oil prices are expensive and scarce due to market distortions, the Government must intervene to control prices so that public welfare is achieved. So in this study, it can be concluded that the Government must intervene in prices when market distortions occur.Penelitian ini bertujuan untuk mengetahui pandangan ekonomi Islam Abu Yusuf terhadap kebijakan pengedalian harga minyak goreng di Indonesia. Metode penelitian yang digunakan adalah metodologi penelitian kualitatif dengan pendekatan kepustakaan (library research). Hasil penelitian menunjukkan bahwa mekanisme pasar dalam Islam bersifat bebas tanpa adanya intervensi. Artinya harga di pasar ditentukan oleh tingkat permintaan dan penawaran yang wajar dan adil (fair price). Namun, pemerintah dapat mengintervensi harga pasar ketika terjadi distorsi pasar. Sehingga ketika harga minyak goreng mahal dan langka akibat distorsi pasar, pemerintah harus turun tangan untuk mengendalikan harga agar kesejahteraan masyarakat tercapai. Maka dalam penelitian ini dapat disimpulkan bahwa pemerintah harus melakukan intervensi harga pada saat terjadi distorsi pasar.